Angioleiomyoma of Uterus: A Clinicopathologic Study of 6 Cases. (February 2018) - Gupta, Mayank; Suryawanshi, Mayur; Kumar, Ramani; Peedicayil, Abraham
Background and Objectives . Angioleiomyoma is a benign perivascular neoplasm commonly involving subcutaneous tissue of extremities, head, and trunk region. They rarely involve the female genital tract. This study analyses clinicopathological features of 6 cases of uterine angioleiomyoma. Methods . Routine sections of 6 cases were reviewed and immunohistochemical markers namely muscle-specific actin, h-caldesmon, desmin, CD10, WT-1, HMB-45, and melan-A were done. Results . Of the 6 cases, 4 cases had tumor involving the corpus and 2 cases had tumor in the cervix. Grossly, all tumors had a whorled and congested cut surface. Microscopic examination of all the cases revealed circumscribed neoplasms composed of interlacing fascicles of benign perivascular smooth muscle cells with evenly distributed slit-like blood vessels (solid variant) along with vessels exhibiting thick muscular walls with swirling pattern (venous variant). In only 2 cases many dilated vessels were seen (cavernous variant). Immunohistochemically, all cases were positive for muscle-specific actin, h-caldesmon, and desmin. All cases were negative for CD10 and WT-1 ruling out endometrial stromal tumor and were negative for HMB-45 and melan-A ruling out perivascular epithelioid cell tumor (both endometrial stromal tumor and perivascular epithelioid cell tumor have prominent vessels but have different histomorphology). In all cases, surgical excision was curative and there were no intraoperative or postoperative complications. Follow-up of all the cases has been unremarkable. Conclusion . As the World Health Organization has not included angioleiomyoma in the classification of mesenchymal tumors of uterine corpus and cervix, we recommend that it should be included in the classification.